Collagen scaffolds with in situ-grown calcium phosphate for osteogenic differentiation of Wharton's jelly and menstrual blood stem cells - Karadas, Ozge; Yucel, Deniz; Kenar, Halime; Kose, Gamze Torun; Hasirci, Vasif (WILEY, 2014)
The aim of this research was to investigate the osteogenic differentiation potential of non-invasively obtained human stem cells on collagen nanocomposite scaffolds with in situ-grown calcium phosphate crystals. The foams had 70\% porosity and pore sizes varying in the range 50-200 mu m. The elastic modulus and compressive strength of the calcium phosphate containing collagen scaffolds were determined to be 234.5 kPa and 127.1 kPa, respectively, prior to in vitro studies. Mesenchymal stem cells (MSCs) obtained from Wharton's jelly and menstrual blood were seeded on the collagen scaffolds and proliferation and osteogenic differentiation capacities of these cells from two different sources were compared. The cells on the composite scaffold showed the highest alkaline phosphatase activity compared to the controls, cells on tissue culture polystyrene and cells on collagen scaffolds without in situ-formed calcium phosphate. MSCs isolated from both Wharton's jelly and menstrual blood showed a significant level of osteogenic activity, but those from Wharton's jelly performed better. In this study it was shown that collagen nanocomposite scaffolds seeded with cells obtained non-invasively from human tissues could represent a potential construct to be used in bone tissue engineering. Copyright (C) 2012 John Wiley \& Sons, Ltd.
Keywords: bone tissue engineering; calciumphosphate; Wharton's jelly; menstrual blood; composite scaffold; mesenchymal stem cells